Ecological risk assessment of heavy metal contamination in Xiaohai Lagoon, Hainan island, China - Eunice Mutethya; Qi Liu; Edwine Yongo; Zhiqiang Guo; Hui Yu; Yunyu Zhang; Zhiyuan Lu; Changqing Ye (Frontiers in Marine Science, 2025)
Xiaohai Lagoon has faced significant natural and anthropogenic pressures, necessitating a heavy metal contamination assessment. Sediment and water samples were collected in 2024 during dry and wet seasons to assess heavy metal pollution and ecological risk based on individual and synergistic indices. Heavy metal content was detected using an inductively coupled plasma mass spectrometer. The Cr, Zn, Pb, Cd, Cu, Ni, As, and Hg in water ranged from 0.90 to 9.08, 4.52 to 49.48, 0.01 to 7.26, 0.00 to 1.33, 0.87 to 61.90, 0.03 to 13.23, 1.16 to 3.04, and 0.01 to 2.00 µg L -1 , respectively. The average heavy metal concentration in water was within acceptable limits. For sediments, Cr, Zn, Pb, Cd, Cu, Ni, As, and Hg contents ranged from 1.98 to 40.60, 8.50 to 90.31, 3.12 to 61.62, 0.00 to 0.25, 0.50 to 76.38, 1.31 to 17.23, 1.27 to 9.41, and 0.00 to 0.06 mg kg -1 , respectively. Sediment metals, except Cd, met China’s primary standards and varied seasonally, with peaks in the dry season. The average geoaccumulation index ( I geo ) values for all the metals, except As, were below 0, while the pollution load index ( PLI ) suggested moderate pollution. Additionally, the contamination factor ( CF ) reflected moderate pollution for Cd and Hg, while As reflected a considerable pollution level. Further, Pearson’s and PCA analyses revealed that Cr, Zn, Pb, Cd, Ni, As, and Hg correlated positively, possibly from aquaculture and agricultural inputs, while Cu derived from urban sources. The study provides critical data for informed management of the Xiaohai Lagoon.